2023
DOI: 10.7759/cureus.45324
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of Red Meat Consumption and the Risk of Cancer

Barath Prashanth Sivasubramanian,
Mihir Dave,
Viraj Panchal
et al.

Abstract: Red and processed meat consumption rates are increasing in the United States. In this review, we present the current evidence that links red meat consumption and cancer development. A literature search was conducted in the PubMed and Google Scholar databases to review red meat consumption and its association with breast cancer and gastrointestinal cancer. Due to the presence of heme iron, which triggers oxidative reactions that eventually result in tumor formation, red meat consumption is strongly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This association has also been investigated by other researchers. A study conducted by Bernstein et al demonstrated a strong correlation between the amount and frequency of meat consumption and colorectal cancer [2,3]. Additionally, studies have noted that increased consumption of grilled, stewed, or processed red meat also raises the risk of colorectal cancer [4].…”
Section: Dear Editormentioning
confidence: 99%
“…This association has also been investigated by other researchers. A study conducted by Bernstein et al demonstrated a strong correlation between the amount and frequency of meat consumption and colorectal cancer [2,3]. Additionally, studies have noted that increased consumption of grilled, stewed, or processed red meat also raises the risk of colorectal cancer [4].…”
Section: Dear Editormentioning
confidence: 99%
“…Colon cancer ranks among the most prevalent cancers globally, particularly in Western nations. Numerous epidemiological studies suggest a potential correlation between the consumption of Western-style diets, rich in elements such as red meat, and an elevated incidence of colon cancer [ 1 ]. In 2019, approximately 2.2 million new cases of colorectal and anal cancer were diagnosed worldwide, resulting in approximately 1.1 million deaths [ 2 ].…”
Section: Introductionmentioning
confidence: 99%